2006
DOI: 10.12693/aphyspola.110.125
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Ion Implantation in GaN: Damage Formation and Recovery

Abstract: Rare earth ions implanted GaN has been investigated by transmission electron microscopy versus the fluence, using Er, Eu or Tm ions at 150 keV or 300 keV and at room temperature. Point defect clusters and stacking faults are generated from low fluences (7 × 10 13 at/cm 2 ), their density increases with the fluence up to the formation of a highly disordered layer at the surface. This highly disordered layer is observed from a threshold fluence of 3×10 14 at/cm 2 at 150 keV and 3×10 15 at/cm 2 at 300 keV, and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been suggested that strain is the driving force for defect transformation in GaN [17,18]. Strain, or more precisely the deformation perpendicular to the sample surface caused by implantation of a thin surface layer, can be directly measured via X-ray diffraction (XRD) which is very sensitive to small variations in the lattice parameter [21][22][23][24]. It was reported previously that the defect nature of extended defects caused by high fluence ion implantation is different in a-plane and c-plane GaN [25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that strain is the driving force for defect transformation in GaN [17,18]. Strain, or more precisely the deformation perpendicular to the sample surface caused by implantation of a thin surface layer, can be directly measured via X-ray diffraction (XRD) which is very sensitive to small variations in the lattice parameter [21][22][23][24]. It was reported previously that the defect nature of extended defects caused by high fluence ion implantation is different in a-plane and c-plane GaN [25].…”
Section: Introductionmentioning
confidence: 99%
“…After implantation, the sample covered by GaN powder was annealed for 30 min at 700 • C, and then for 30 min at 1200 • C, each time with a nitrogen overpressure of 1 GPa. Such a procedure allowed for the use of higher annealing temperatures for better lattice damage recovery and optical activation of ytterbium while minimizing the risk of surface dissociation, the formation of nitrogen vacancies, and the diffusion of implanted ytterbium from inside the crystal to the crystal surface [19,[52][53][54][55][56]. Ion implantation followed by thermal annealing to recover implantation damage and to optically activate the RE 3+ ions is a common method of obtaining RE-doped GaN [8-11, 14, 15, 19, 20, 34-37, 45, 46, 56]; however, annealing with nitrogen overpressure is rarely done, mainly due to the lack of the unique equipment which is necessary to perform such a process.…”
Section: Sample and Experimental Techniquesmentioning
confidence: 99%